METHODS FOR REDUCING PSYCHOLOGICAL DISTANCE BETWEEN PARENTS AND ADOLESCENTS - Ibragimova Rano Jalgasovna (Bright Mind Publishing, 2025)
This article examines methods for reducing psychological distance between parents and adolescents during the teenage years. The findings indicate that open communication, emotional intelligence development, creating a trusting environment, and individualized approaches are effective methods for reducing psychological distance. This research can serve as a practical guide in the field of family psychology.
Keywords: Adolescence, family psychology, parent-child relationships, psychological distance, communication.